Molecular methods of measurement of hepatitis B virus, hepatitis C virus, and human immunodeficiency virus infection: implications for occupational health practice - Kao, J. H. (BMJ Group, 1999)
Over the past decade, several molecular techniques for the detection of human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV) have been developed that have implications for occupational health practice. This review describes the techniques used for qualitative and quantitative detection of the viral genome, and briefly explains nucleic acid sequencing and analysis of phylogenetic trees. The review also discusses the current and potential uses of these techniques in investigations of transmission of bloodborne viruses by patient to worker and worker to patient, in the management of occupational exposure to blood, in research, and in the development of guidance and policy on infected healthcare workers who perform procedures prone to exposure.